Environment Friendly, Efficient Chloroacetic Acid Promoted Synthesis of 1-Amidoalkyl-2-naphthols Under Neat Condition - Duvedi, Robita; K. Singh, Rajesh (Asian Journal of Chemistry, 2012)
An environment friendly synthesis of 1-amidoalkyl-2-naphthols was developed by one-pot reaction of 2-naphthol with various aldehydes and urea or amides catalyzed by chloroacetic acid in the absence of solvent media under thermal and microwave irradiation conditions. This greener protocol offer many advantages such as shorter reaction times, simple work-up and excellent yield.